2018
DOI: 10.1177/0017896918763462
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors for adolescents’ illicit drug use: A population-based study

Abstract: Objective: The use of illicit drugs by adolescents is a widespread problem in Taiwan. The aim of this study was to identify risk and protective factors. Design: Web-based survey of high school students. Setting: Senior high schools and vocational high schools in northern Taiwan. Method: Survey data were collected from 15,754 students. Logistic regression analysis examined potential risk and protective factors in individual, family and peer/school domains for lifetime, past-year and past-month illicit drug use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…An earlier study revealed that adult perceptions influenced their practices of mentoring [ 44 ]. The perspectives of some staff, who loaded onto groups 1 and 4, were in line with earlier research in that peer influences were one of the most significant contributors to drug use among adolescents [ 6 , 45 , 46 ]. These staff emphasized external influences during supervision, whereas others prioritized internal influence.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…An earlier study revealed that adult perceptions influenced their practices of mentoring [ 44 ]. The perspectives of some staff, who loaded onto groups 1 and 4, were in line with earlier research in that peer influences were one of the most significant contributors to drug use among adolescents [ 6 , 45 , 46 ]. These staff emphasized external influences during supervision, whereas others prioritized internal influence.…”
Section: Discussionsupporting
confidence: 78%
“…Designated Q statements were provided to address the raised issues related to drug use prevention during supervisory interactions. The statement sentences were developed according to a literature review [ 6 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] and experiences of youth counsellors. The research team discussed the draft statements with two senior youth counsellors; both worked with students of drug use problem for more than 10 years.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Drug use has been a critical health problem among students over the past decade. Prevalence rates for lifetime, past-year, and past-month illegal drug use were 2.79%, 1.91%, and 1.72%, respectively, for 15,754 senior and vocational high school students in Taiwan [1]. A national campus survey in 2017 showed drug-use prevalence at 0.23% for junior high school students and 0.73% for senior high school students [2].…”
Section: Introductionmentioning
confidence: 99%